Review Article on The Current Status of Food Items and Food Contamination Chain in Bangladesh - Mrityunjoy Acharjee; Raquiba Sultana; Kamal Kanta Das; Md Sharifull Islam (Indonesian Food and Nutrition Progress, 2026)
Nowadays, people of Bangladesh are facing various foodborne diseases due to the consumption of unhygienic food items such as street foods, mid-level or high-level restaurant foods, vendor juices, unhygienic fermented foods, and so on. Behind this illness, a group of foodborne pathogens is responsible, which become associated with the foods during unhygienic processing, handling, supplying, and storage. People from different socioeconomic backgrounds and a variety of ages consume these foods as the foods are sold at an affordable price with a satisfactory taste. However, this causes a high morbidity and sometimes a mortality rate in Bangladesh. Therefore, proper steps should be taken to provide safe, healthy, and hygienic food to consumers. This review article was conducted over the last 8 years, from 2014 to 2021 to reflect the importance of different food items in Bangladesh, as well as the present unhygienic status of these foods, foodborne pathogens associated with the diseases caused by the consumption of these foods.